Application of Comprehensive Geophysical Prospecting Method in the Exploration of Coal Mined-Out Areas - Xiao Luo; Shuang Gong; Zhonggang Huo; Hongyan Li; Xinpin Ding (Advances in Civil Engineering)
Due to the influence of mining technology, some coal mines will leave mined-out areas (or goafs) in the rock mass after mining. If the distribution law and influence scope of mined-out areas cannot be accurately explored and controlled, it will bring great potential safety hazards to subsequent coal mining and cause serious harm to adjacent houses, roads, bridges, railways, and so on. The unmanned aerial vehicle (UAV) aerial survey is used to accurately acquire the three-dimensional model of the slope in the key area of Yuanbaoshan open-pit coal mine, which provides basic information for the real-time visualization of the open-pit mine and the establishment of the engineering geological research profile. And the distribution of mined-out areas and water accumulation in the coal mine are investigated in detail by using the comprehensive geophysical prospecting method of the transient electromagnetic method (TEM) and controlled source audio-frequency magnetotellurics (CSAMT). Then, the borehole detection method is used to verify the goaf range obtained from comprehensive geophysical prospecting, and the results show good consistency. In addition, based on the results of borehole exploration and the comprehensive analysis of the borehole image, the instantaneous water level elevation in goaf and the development height of the water-conducting fracture zone and caving zone are concluded. Finally, the distribution of coal mined-out areas in the exploration area is obtained, and the results show that through the use of the transient electromagnetic method and controlled source audio-frequency magnetotellurics method, combined with drilling detection methods, the purpose of accurate exploration of mined-out areas in coal mines can be achieved.